XX квартал Херсонеса у XIII ст. (за даними археології та матеріальних пам’яток) - Залеська, В.М.; Калашник, Ю.П. (Археологія, 1992)
У статті розглядаються результати розкопок експедиції Держ. Ермітажу в одному з центральних кварталів північного району Херсонеського городища, які розкривають картину життя пізньовізантійського будинку, знищеного пожежею, що охопила все місто. Матеріали, які публікуються вперше, — пам'ятки художнього бронзового литва, кераміка місцева та імпортна (походить з М. Азії і Волконського п-ва) — містять нові дані для датування загибелі міста. После катастрофы, постигшей Херсонес в конце X или на рубеже X—XI вв., строительство в исследуемой части северного района возобновилось, по-видимому, в начале XIII в.; окончательно здесь жизнь прекратилась вследствие грандиозного пожара, охватившего весь город. Своеобразие XX квартала состояло в том, что он представлял собой пустырь, на котором располагались три жилых дома. Зажиточный владелец усадьбы III, используя выгоду положения дома на оживленном перекрестке, устроил в нем помещения для лавки. Судя по наличию в доме литургической утвари, его хозяин мог быть священнослужителем. Находки на полу в слое горения монет времени Латинской империи и никейских императоров позволяют датировать пожар, погубивший как этот дом, так и все постройки северного района, 20—70-ми гг. XIII в. Среди найденных в доме III образцов бронзового литья особый интерес представляют энколпион с изображением св. Фотия, свидетельствующий о связях Херсонеса с Никомидией, и две мощехранительницы, одна из которых уникальна. В декоре многих глиняных сосудов из домов XX квартала, как импортных, так и местных, в том числе оригинального водолея, заметно сильное воздействие восточных художественных традиций. Following the disaster that overtook Hersones in the later X century or on the turn of the X and XI centuries the construction of the examined section of the northern district was probably resumed in the early XIII century. Life finally came to an end there as a result of a vast fire that enveloped the whole city. The peculiarity of block XX was the waste-land with three apartment houses situated on it. A well-do-to owner of the house III opened a store there, taking advantage of the house’s location at the busy cross-roads. Judging by the church-plates discovered in the house the owner could be a clergyman. Some coins of the Latin empire and Nicaean emperors times were found on the floor, in the burning layer, enabling to date the fire that destroyed not only that house but all the buildings of the northern district back to the 20ies—70ies of the XIII century. Among the bronze castings found in the house III, enkolpion (a variety of a cross) with St. Fotiy’s picture on it testifying to Hersones’s ties with Nicomidia, as well as two cases for keeping holy relics, one of which was a unique one, were of special interest. The decoration of the pottery articles from the block XX houses, both imported and local, the original Acquarius picture including, is recognized to be greatly influenced by the eastern artistic traditions.